NG-Circos: next-generation Circos for data visualization and interpretation. Issue 3 (3rd September 2020) - Cui, Ya; Cui, Zhe; Xu, Jianfeng; Hao, Dapeng; Shi, Jiejun; Wang, Dan; Xiao, Hui; Duan, Xiaohong; Chen, Runsheng; Li, Wei
Abstract: Circos plots are widely used to display multi-dimensional next-generation genomic data, but existing implementations of Circos are not interactive with limited support of data types. Here, we developed next-generation Circos (NG-Circos), a flexible JavaScript-based circular genome visualization tool for designing highly interactive Circos plots using 21 functional modules with various data types. To our knowledge, NG-Circos is the most powerful software to construct interactive Circos plots. By supporting diverse data types in a dynamic browser interface, NG-Circos will accelerate the next-generation data visualization and interpretation, thus promoting the reproducible research in biomedical sciences and beyond. NG-Circos is available at https://wlcb.oit.uci.edu/NG-Circos and https://github.com/YaCui/NG-Circos .